Crystallography and interfacial structure in a directionally solidified Al2O3/Y3Al5O12/ZrO2 eutectic crystal. (1st March 2018) - Wang, Xu; Zhong, Yujie; Sun, Qian; Li, Yiran; Zhang, Wen; Qi, Dongqing; Wang, Dong; Jiang, Bailing
Abstract: The single crystal of Al2 O3 /Y3 Al5 O12 /ZrO2 ternary eutectic was prepared by an optical floating zone furnace. The crystallography and interfacial structure of the directionally solidified ternary eutectic were investigated by means of electron backscattered diffraction and transmission electron microscopy. We found that the preferred crystallographic orientation of the Al2 O3 /Y3 Al5 O12 /ZrO2 eutectic crystal was { 11 2 ¯ 0 }〈 1 1 ¯ 00 〉Al2 O3  ||{001}〈001〉Y3 Al5 O12  ||{001}〈001〉ZrO2 . Most of the tiny ZrO2 locates dispersively between Al2 O3 and Y3 Al5 O12 . It can be concluded that interfacial energy between Al2 O3 -Y3 Al5 O12 -ZrO2 played an important role in deciding the preferred crystallographic orientations of the Al2 O3 /Y3 Al5 O12 /ZrO2 eutectic and the precipitation behavior of the ZrO2 phase. Graphical abstract: